MEMORABLE TOURISM EXPERIENCES AND ITS RELATIONSHIP TO BEHAVIOURAL INTENTION - Kumar, R. Satheesh; S.J, Ajith Kumar; Shirlvin Nigli, Keith; Dabral, Paritosh; Rawath, Sushma (International Journal of Research -GRANTHAALAYAH, 2022)
Experiences form a major role for a tourist to decide whether he/she has to take up tourism activities for a particular destination. These experiences can be a positive one or a negative one. This research study was conducted to identify the factors of memorable tourism experience of travelers and its relationship with behavioral intention. The present study has thrown the light on know how people choose the particular destination based on their experiences and what is their behaviour towards the experience recorded. The main focus was to extract factors of memorable experiences and behaviour intentions of tourists all over the world and to find out whether experience really has some impact on the travelers behaviour.